The Role Of Regular Physical Acitivity In Improving Fitness And Cardiovascular Health Of Sport Science Students 2025 Using The TKJI 1200 Meters - Agneta Grace Sesilia; Rivan Adriza Fahlevi; Rizki; M. Arief Setiawan; Ns. Zaky Mubarak (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This research aims to examine the role of regular physical activity in improving physical fitness and cardiovascular health among Sports Science students in 2025 using the Indonesian Physical Fitness Test (TKJI) 1200-meter run as a measurement instrument. This study employed a descriptive method with a quantitative approach conducted at the UNSIKA football field. Sixteen students participated as research samples. The measurement results showed that eight students were in the “Very Poor” category, six students in the “Poor” category, one student in the “Fair” category, and one student in the “Good” category. These findings illustrate that most students still have a low level of cardiorespiratory fitness. This study emphasizes the importance of regular physical activity such as aerobic exercise to increase VO₂ max capacity, improve heart efficiency, and reduce the risk of cardiovascular diseases. The findings are expected to serve as a basis for developing physical fitness programs for students and the general public.